Songs from Overseas: Music Downloading as a Marker of Migration - Woolhous, Matthew; Tidhar, Dan (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2020)
Findings from the Digital Music Lab in Association with Nokia at McMaster University are reported. Diasporas and migration patterns are studied by comparing the popularity of genres in their “mother” country, i.e. place of origin, with their popularity in subsequent host countries. The human stories that underlie these comparisons, whether related to work, war, famine, or simply the desire to “seek a better life” are, where possible, linked to the research findings.